Legacy effects of historical grazing affect the response of vegetation dynamics to water and nitrogen addition in semi‐arid steppe. Issue 2 (5th February 2018) - Chen, Qing; Wang, Zhong‐Liang; Zou, Chris B.; Fan, Yonghui; Dittert, Klaus; Lin, Shan
Abstract: Question: Climate change interacts with land use and introduces new pressures that trigger growing concerns about increasing vulnerability of the Eurasian steppes. However, it is not well known how increasing precipitation and atmospheric N deposition interact with the land use legacy to affect nutrient availability, plant species composition and therefore vegetation dynamics of the Mongolian Steppe. Location: Steppe in Xilin River Basin, Inner Mongolia, China. The mean annual precipitation is 343 mm with 60%–80% of it occurring during the plant growing season. Methods: We conducted a 6‐years (2005–2010) field experiment to manipulate N and water availability on sites experiencing two different historical stocking rates. Species composition, above‐ground biomass and plant N concentration were determined at both individual and community levels. Soil cumulative inorganic N and N mineralization rates were determined by laboratory incubation. Results: (1) Supplementary irrigation increased soil cumulative inorganic N and N mineralization rate, plant community N uptake, and the abundance of perennial species for the site with high historical stocking rate. In contrast, long‐term water addition decreased soil cumulative inorganic N and N mineralization rate, and did not change the plant community N uptake, but increased the abundance of Cleistogenes squarrosa as a species indicative of degradation for sites with moderate historic stocking rate. (2) Nitrogen addition increased soil cumulative inorganic N and N mineralization rate irrespective of grazing history under ambient precipitation, and resulted in a burst of annuals in moist years at both sites. Under supplementary irrigation, N addition increased soil cumulative inorganic N and N mineralization rate at the site with moderate historic stocking rate, but not at the site with high historical stocking rate, and increased the abundance of taller perennial species at both sites. Conclusions: Legacy effects of grazing greatly affect plant composition responses to increasing water and N availability. The effectiveness of N application in restoring heavily degraded sites in the Mongolian steppe depends on precipitation availability. In the face of increasing precipitation and atmospheric N deposition, resource managers should be prepared to cope with the different vegetation succession and recovery trajectories as a result of historical land‐use difference. Abstract : Legacy effects of grazing greatly affect the plant composition responses to increasing water and nitrogen availability. Long‐term increase in precipitation may lead to more N limitation for plant growth at the moderately gazed site than at the heavily gazed site. The effectiveness of N application in restoring heavily degraded sites in the Mongol Steppe depends on precipitation availability.